1987
DOI: 10.1161/01.hyp.9.5.451
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular hypertension identified by captopril-induced changes in the renogram.

Abstract: Radioisotope renography was performed in 21 patients with hypertension and unilateral renal artery stenosis with and without premedication with 25 mg of captopril, and the results were compared with the effect of percutaneous transluminal angioplasty on the blood pressure, assessed 6 weeks after angioplasty. Angioplasty caused a considerable decrease in blood pressure in 15 of the 21 patients. In 12 of these 15 patients, captopril induced changes in the time-activity curves of the affected kidney only, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
6

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 12 publications
1
32
0
6
Order By: Relevance
“…The results reported here extend our preliminary observations 38 and those of Geyskes and associates 12 that the presence of captopril-induced changes effectively differentiates functional from anatomic renal artery stenosis. We hypothesized that a normal precaptopril scan that remains normal after captopril administration suggests essential hypertension, perhaps in the setting of coincident but subcritical renal artery obstruction, and that an abnormal (using our criteria) precaptopril scan that does not change after drug administration indicates a fixed or irreversible renal ischemic lesion.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The results reported here extend our preliminary observations 38 and those of Geyskes and associates 12 that the presence of captopril-induced changes effectively differentiates functional from anatomic renal artery stenosis. We hypothesized that a normal precaptopril scan that remains normal after captopril administration suggests essential hypertension, perhaps in the setting of coincident but subcritical renal artery obstruction, and that an abnormal (using our criteria) precaptopril scan that does not change after drug administration indicates a fixed or irreversible renal ischemic lesion.…”
supporting
confidence: 90%
“…We also examined whether captopril induced changes in the scintigram. 12 A scan with captopril-induced changes was one in which a normal time to peak activity and/or glomerular filtration rate ratio became abnormal following the administration of the drug. A renal arteriogram was judged positive for atherosclerotic renal artery stenosis if an obstruction of greater than 75% was present.…”
Section: Study Criteriamentioning
confidence: 99%
“…Among these 4, two kidneys had stenosis of accessory RA with normal main RA and one kidney was poorly functioning. 11 Captopril Tc99m-DTPA Sensitivity-80%, Specificity-100% Nally JV et al (1988) 12 Captopril Tc99m-DTPA Sensitivity-100%, Specificity-100% Safakianakis GN (1989) 13 Captopril-131-OIH Sensitivity-100%, Specificity-100% Svetkey LP et al (1989) 14 Captopril Tc99m-DTPA Captopril-131-OIH Sensitivity-91%, Specificity-50% Sensitivity-80%, Specificity-42% Charles C et al (1990) 15 Captopril Tc99m-DTPA Without Captoril Sensitivity-91%, Specificity-93% Sensitivity-43-68% Kakizaki H et al (1992) 16 Captopril Tc99m-DTPA Sensitivity-86%, Specificity-100% Man SJ etv al (1992) 17 Captopril Tc99m-DTPA Sensitivity-93%, Specificity-95% 18 …”
Section: Resultsmentioning
confidence: 99%
“…27 As far as ACE inhibitor scintigraphy is concerned there are many studies available which are shown in Table 1, but yet there is no consensus on scintigraphy protocol including radiopharmaceutical, sequence of studies, ACE inhibitors, their dose and specific criteria. [8][9][10][11][12][13][14][15][16][17][18][19][20] Nally JV et al achieved the sensitivity and specificity of 100% and their criteria for positive test were decrease in maximum activity, delayed uptake, widening of peak activity and slowing the excretory phase. 12 But on contrary , Kumar r et al and Orellana P et al showed lower sensitivity of 44.4% and 60.9% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation